2001
DOI: 10.1111/j.1475-2743.2001.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of tillage on soil displacement of hilly areas used for growing wheat in Greece

Abstract: Abstract. Tillage displaces large amounts of soil from upper slopes and deposits soil in lower landscape positions, greatly affecting productivity in these areas. The long‐term effect of tillage on soil erosion was studied in four field sites growing mainly rainfed wheat. The soil loss from landscape positions with slopes, ranging from 3 to 28%, was estimated by: (a) comparing data of horizon thickness described at the same position at different times; and (b) using soil movement tracers added to the soil. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 16 publications
2
22
0
3
Order By: Relevance
“…Within 15-tillage operations plot, aboveground biomass and grain yield in top slope positions averaged 0.45 and 0.16 kg/m 2 , respectively, 24-29% and 33-41% lower than those between middle slope and slope bottom (Table1). This indicates that soil loss by tillage causes the reduction in crop production, which agrees on previous studies [3,9,11,14]. Taking the eroded areas into account, aboveground biomass and grain yield averaged only 0.30 and 0.10 kg/m 2 under 5-tillage operations, 0.25 and 0.09 kg/m 2 under 15-tillage operations, respectively.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Within 15-tillage operations plot, aboveground biomass and grain yield in top slope positions averaged 0.45 and 0.16 kg/m 2 , respectively, 24-29% and 33-41% lower than those between middle slope and slope bottom (Table1). This indicates that soil loss by tillage causes the reduction in crop production, which agrees on previous studies [3,9,11,14]. Taking the eroded areas into account, aboveground biomass and grain yield averaged only 0.30 and 0.10 kg/m 2 under 5-tillage operations, 0.25 and 0.09 kg/m 2 under 15-tillage operations, respectively.…”
Section: Resultssupporting
confidence: 87%
“…wheat, corn, and sweet potato) on the hilltop positions were half of that at the bottom positions, or even less [2]. Case studies have also demonstrated that there were higher grain yields or biomass production in areas of soil accumulation by tillage compared with areas of soil removal by tillage [3,9,11,14]. For example, an investigation conducted in hilly areas in west central Minnesota reported that wheat yields in areas of soil loss by tillage were 50% lower than those in areas of soil deposition [11] .…”
Section: Introductionmentioning
confidence: 96%
“…Close relationships between the spatial distri bution of tillage erosion and the spatial pat terns of total C, N, P, texture, soil depth, rock fragment cover and above ground biomass have been reported (Van Oost et al, 2000b;Kosmas et al, 2001 ;Quine and Zhang, 2002;Li et al, 2004;Heckrath et al, 2005). These results have provided evidence that tillage erosion operates like a conveyor belt, trans ferring soil and associated constituents from convexities to concavities.…”
Section: Consequences Fo R Soil Qualitymentioning
confidence: 99%
“…At present, there are over 80 research papers in the literature that specifically deal with tillage erosion (Figure 1) Initially, these studies focused on the experimental identifi cation of controlling variables and the assess ment of tillage erosion rates (tTDstly using and productivity in various agro-ecological environments have been documented (Li and Lindstrom, 2001, Kosmas et al, 2001, de Alba, 2001, Quine and Zhang, 2002da Silva and Alexandre, 2004, Li et al, 2004, Heckrathet al, 2005 and tillage erosion sim ulation tTDdels have been developed (Covers et al, 1996;Van O:lst et al, 2000b;2003b;de Alba, 2003, Schoorl et al, 2004Quine and Zhang,2004c) While early studies on tillage erosion strongly focused on mechanized agriculture, recent studies have shown that substantial tillage erosion also occurs in devel oping countries with animal or man powered tillage tools, especially when tillage is per formed in dissected landscapes on steep slopes (Kirm. ro et al, 2005;Turkelboomet al, 1997;, Thapaet al, 1999a1999b;Quine et al, 1999b;1999c;Nyssen et al, 2000;Dercon et al, 2003;Zhang et al, 2004b) Consequently, tillage erosion is now recog nized as an important global soil degradation process that has to be accounted for when assessing tre erosional impacts on soil produc tivity (eg, Heckrath et al, 2005), erNironmental 1992199619982001 Figure I Temporal evolution and typology of tillage erosion research papers in literature Source: Web of Science.…”
Section: Introductionmentioning
confidence: 99%
“…Although tillage can help to overcome some soil-related constraints to crop production, it can result in deterioration of soil structure, reduced infiltration, increased runoff and erosion, water pollution, and degradation of the soil (Lal, 1991). Conventional soil cultivation systems, which include intensive and continuous soil tillage, are often responsible for severe soil degradation and possible loss of crop productivity Tsara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%